ALIH KODE BAHASA INDONESIA-BAHASA BUGIS DALAM CERAMAH AGAMA ISLAM (Indonesian-Buginese Languages Code Switching in Islamic Preaching) - M. Ridwan (Balai Bahasa Sulawesi Selatan, 2014)
The writing proposes language usage of Indonesian-Buginese language code switching and vice versa ofIslamic preaching in Masjid Nurul Iman, Sinjai Borong District of Sinjai Regency. Method used is descriptive.The data obtained is sentence characterized with code switching of Islamic preaching conveyed in MasjidNurul Iman, Sinjai Borong District of Sinjai Regency. Result of research shows that the preacher and theaudience are mutual intelligible in using Buginese language. In addition, the preachers also sometimes speakin Indonesian language as welcoming preaching or prolog of formality form. The use of Indonesian-Buginesecode switching and vice versa is a way to estalish good relations between Buginese speakers. Code switchingis one aspect of interdependency language in multilingual society. In the code switching case of either twolanguages or more, it is marked by (1) each language still support its own function based on the context, (2)the function of each language is in accordance with the relevant situation of contextual change. They becomethe reason of language switching in preaching found in Masjid Nurul Iman. The switching of code is done bythe preachers since they are difficult to find relevant and right words which are easier to understand by theaudience.